RESPONSIBILITY OF THE BOARD OF DIRECTORS FOR VIOLATIONS OF GOOD CORPORATE GOVERNANCE PRINCIPLES IN THE MANAGEMENT - Thelisia Kristin; Amad Sudiro; Nicolaas Sugiharta (Indonesia Private Law Review, 2022)
Taking into account the provisions of the Articles of the Limited Liability Company Law, it can be stated that there are no provisions governing the application of the GCG principles. because it only stipulates that the company is obliged to comply with all good things in a corporation, but it does not regulate the forms of GCG. itself, the procedures for implementing GCG, what are the responsibilities of a Board of Directors if the principle is violated and what are the sanctions that must be given to those who violate it. In that regard, this norm can certainly cause legal uncertainty. This paper use normative legal research method. Management responsibilities may emerge if there is a violation of GCG principles in the management of PT which can be in the form of: Civil and criminal liability.